10th International Conference on Nuclear Engineering, Volume 3 2002
DOI: 10.1115/icone10-22439
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Loss-of-Coolant Accident Using MAAP4.03 and RELAP5/MOD3.2.2

Abstract: Analysis was performed for a large-break loss-of-coolant accident (LOCA) in the APR1400 (Advanced Power Reactor 1400 MWe) with the thermal-hydraulic analysis code RELAP5/ MOD3.2.2 and the severe accident analysis code MAAP4.03. The two codes predicted different sequences for essentially the same initiating condition. As for the break flow and the emergency core cooling (ECC) flow rates, MAAP4.03 predicted considerably higher values in the initial stage than RELAP5/ MOD3.2.2. It was considered that the differin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, it produces reasonable prediction capabilities comparable to MELCOR and SCDAP [16]. MAAP4 is widely used in Korea in severe accident analysis and level 2 PSA for APR1400 design [17,18]. A noding diagram for APR1400 is shown in Figure 3.…”
Section: Design Characteristics To Cope With Extended Sbomentioning
confidence: 99%
“…However, it produces reasonable prediction capabilities comparable to MELCOR and SCDAP [16]. MAAP4 is widely used in Korea in severe accident analysis and level 2 PSA for APR1400 design [17,18]. A noding diagram for APR1400 is shown in Figure 3.…”
Section: Design Characteristics To Cope With Extended Sbomentioning
confidence: 99%
“…However, information from these is often too conservative to perform a realistic PSA for a riskinformed application [3]. In the last years a few comparative studies were performed to justify the use of MAAP4 for the PSA Level 1 analysis of advanced reactors [4,5]. In the comparison between MAAP4.07 and S-RELAP5 for U.S. EPR reactor [4] MAAP4 has demonstrated that it is a rather good simulator of nuclear plant transient trends.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there are certain nuclear plant scenarios for which MAAP4 is clearly not applicable, such as early transient of large-break LOCA (at break sizes beyond the area of the largest attached pipe). In the study for APR1400 (Advanced Power Reactor) [5] comparison between MAAP4.03 and RELAP5/MOD3.2.2 was done for large break loss-of-coolant accident (LOCA). It was concluded that for a more mechanistic simulation of the initial stage of the LOCA using MAAP4.03, more detailed calculations of the primary system are required.…”
Section: Introductionmentioning
confidence: 99%